The reformed doctrine of irresistible sanctification - Partee, C. (Acta Theologica, 2002)
The Reformed confession of “Grace Alone” obviously involves the doctrines of faith, election, justification and perseverance. The conception of irresistible grace is comfortably applied to the same doctrines. However, sanctification is a special case in that the theological focus shifts from divine action to human effort. This emphasis on human striving must avoid the Catholic view of works righteousness, and reject the Thomistic teaching on cooperative grace and condign merit. Analysis of these issues raises again the question of the proper use of human reason in theological reflection.